Assessment of Psychosocial Risks in Workers in the Health Sector: Evidence in the Peruvian Population - Ingrid Pamela Carazas-Bruno; Sandro Rogelio Martínez-Aronés; Dany Yudet Millones-Liza; Miluska Villar-Guevara (My University, 2024)
Health service providers are exposed to serious risks of physical and mental illnesses, thus creating an environment prone to psychosocial risks due to the nature of their work and its implications; it is necessary that they enjoy well-being to guarantee the safety and quality of care. care they provide to patients; this study aims to describe the prevalence of psychosocial risks in health workers, as well as to identify if sociodemographic factors are associated with this risk; for this purpose, a descriptive, association, quantitative and non-experimental study was applied to an initial sample of 2158 workers. The results show that age, gender, work modality and level of education are associated with psychosocial risks; in this sense, it is recommended to implement policies led by the human resources department in order to create a culture that values and prioritizes the mental and emotional well-being of employees. Received: 16 December 2023 / Accepted: 20 March 2024 / Published: 5 May 2024
Keywords: Psychosocial; Population; Environmental health; Psychology; Applied psychology; Business; Medicine; Psychiatry; Psychosocial; Population; Environmental health; Psychology; Applied psychology; Business; Medicine; Psychiatry; Social Sciences Psychology Social Psychology Stress and Burnout Research